Dampak Pelaksanaan Multilateral Naval Exercise Komodo Terhadap Diplomasi Maritim Indonesia - Muhammad Rezky Hafidzzur Rahim; Agussalim Burhanuddin (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Multilateral Naval Exercise Komodo (MNEK) is Indonesia's concrete effort to strengthen maritime diplomacy and the role of the Indonesian Navy (TNI AL) in the context of international relations. MNEK has been implemented four times starting from 2014 to 2023. MNEK is an active diplomatic initiative to build bilateral and multilateral relations, increase preparedness, and strengthen cooperation in responding to natural and humanitarian disasters. In its series of preparations, MNEK involves planning stages, namely the Initial Planning Conference (IPC), Middle Planning Conference (MPC), and Final Planning Conference (FPC), and involves the participation of various countries united in efforts to overcome common challenges. The implementation of MNEK has had a positive impact on Indonesia's maritime diplomacy by building trust building, strengthening a positive image, and making Indonesia a key player in global maritime cooperation.